If z = 10 , find the value of z3 - 3( z - 10)

10*10*10-3(10-10) = 1000-0 = 1000

  • 0

10*3 - 3 ( 10 - 10 )

30-3(0)

27*0

0

  • 0

10*3 -3(10-10)

30-3(0)

30-0

30

  • 0

o

  • -1

10*3-3(10-10)

30-3*0

=0.hi i am only in 6th std but i am trying to answer this question. am i right

  • -2

 z=10

z3-3

10*3-3

30-3

27 ans

  • 0

 z=10

z*3-3(z-10)

10*3-3(10-10)

(30-3)*0

= 0

  • 1

=10*3-3(10-10)

=(30-3)*0

=0

  • 0
answer is 1000
 
  • 0
Z=10
So,Zx3=30
10-10=0
=>30-0
=>0
  • 0
Answer is 1000


Answer is 1000

  • -4
10*10*10-3*0=1000-0=1000
  • 2
Z3 -3(z-10) ;Ans=1000
  • 0
Answer=997
  • 0
30 is the answer
  • 0
30-3(10-10)
30-3*10--3*10
30-30-30
=0
  • 1
ANS=0
 
  • 0
30(thirty)
  • 0
If z = 10
Therefore = z3 - 3 ( z - 10 )
= z3 - 3 x z - 10
= 10 x 3 - 3 x 10 - 10
= 27 x ( 10 - 10 )
= 27 x 0 
= 0
  • 1
z=10
z3-3 (z-10)
10?3-3(10-10)
30-3(0)
30-0
0
  • 1
Ans finally student30
  • 0
z=10
Then
=z3-3(z-10)

=10*3-3(10-10)

=30
  • 0
z3-3(z-10)
z=10
10*3-3(10-10)
30-3*0
30-0
=30
  • 1
Here is your answer.

  • 0
answer 30. 30-3(10-10)=30-3x0=30-0=30
  • -1
ans is 30
 
  • 0
Answer=30
 
  • 0
z3-3(z-10)
10*3-3*10-10
260

 
  • 0
=10*3-3(10-10)
=30-3(10-10)
=27(10-10)
=270-270
=0
  • 0
30 is the answer
  • 0
1000 is the answer
 
  • -1
zero
  • 1
Please find this answer

  • 0
The answer is z*10-3=z7 the answer is z7.
  • -1
Sorry
  • -1
The answer is 10*10-3=100-3=997. The answer is 997
  • -1
The answer is z=10; 10*3=30; 30-3=27
  • -1
ans is 30
  • -1
980 is answer if z3 means z cube
  • -1
Hii
Equation- z3- 3(z-10)
Where z=10
Then,
10?3-3(10-10)
10?3-30+30
30-30+30
30-60
-30. Ans

Here we have first removed the bracket. As we know if before bracket there is minus sign then sign in the bracket changed.
Then we applied BODMAS rule.
  • -1
Answer is 30
  • 0
The answer is 37
  • 0
z3-3(z-10). (z=10) = 10 x 3 - 3(10- 10) =30 -3 x 0 =30 - 0 =30 So z3-3(z-10) is 30
  • 0
10?3-3(10-3)= 30-3(10-3)=27?7=154
  • 0
30
 
  • 0
30 is the correct answer ..
  • 1
    = 10*3-3(10-10)
    = 30-3*0
    = 30
  • 0
=10*3-3(10-10)
=10*0
=0
  • -1
10?3-3(10-10)
30-3?0
27?0
0
  • 0
0 is answer
  • 1
=10?3-3(10-10)
=30-30-30
=-30......
  • 0
If z = 10

= z3 - 3 ( z - 10 )
= z3 - 3 x z - 10
= 10 x 3 - 3 x 10 - 10
= 27 x ( 10 - 10 )
= 27 x 0?
= 0
  • 1
Hi, solve it yourself.
 
  • 1
27 is answer
  • -1
the ans. is 1000
  • 0

 

Put z = 10 in z3 -  3(z - 10), we get
103 -  3(10 - 10) = 1000 
  • 1
0 is the answer
  • 0
0 is the answer
  • 0

z3-3(z-10)
z=10
10*3-3(10-10)
30-3*0
30-0
=30
    • 0
    GIVE
    Z=10
    =Z3-3(Z-10)
    =10*3-3(10-10)
    =30-3(10-10)
    =27*0
    =0
    • 0
    What are you looking for?